La tutela di genere nel dritto matrimoniale canonico: forme e casi - Galluccio, Mariangela (Daimon, 2018)
Gender-equality protection in Matrimonial Canon Law: Formsand cases The article focuses on the role of the woman in the canonical marriage, a contract and a sacrament in which the woman has equal rights to the man, and that can be considered as a model of mutual and equal relationship between man and woman. The canonical marriage protects gender-equality both during the stage that precedes entry into marriage, and with any subsequent checks on the valid constitution of the bond of matrimony